2015
DOI: 10.1093/ije/dyu257
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Profile: FAMILY Cohort

Abstract: The FAMILY Cohort is a longitudinal study of health, happiness and family harmony (the '3Hs') at individual, household and neighbourhood levels in Hong Kong. Using a family living in the same household as the sampling unit, the study (n = 20 279 households and 46 001 participants) consists of a composite sample from several sources, including: a population-representative random core sample (n = 8115 households and 19 533 participants); the first-degree relatives of this sample (n = 4658 households and 11 063 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…The CD-RISC was administered face-to-face by trained interviewers during Wave 2 of household visits. The follow-up rate for the household visits was 70.7 %, and the Cohen's w effect size for differences in non-response in Wave 2 was small (\0.1) [7]. Compared with Hong Kong census statistics from 2011, households living in public housing and households with low monthly household income were over-represented in the random core sample.…”
Section: Participantsmentioning
confidence: 88%
See 1 more Smart Citation
“…The CD-RISC was administered face-to-face by trained interviewers during Wave 2 of household visits. The follow-up rate for the household visits was 70.7 %, and the Cohen's w effect size for differences in non-response in Wave 2 was small (\0.1) [7]. Compared with Hong Kong census statistics from 2011, households living in public housing and households with low monthly household income were over-represented in the random core sample.…”
Section: Participantsmentioning
confidence: 88%
“…The sample was derived from the FAMILY Cohort, a prospective population-based cohort study, described in detail elsewhere [7]. The sampling unit was a family living in the same household, and all family members aged 10 and above were invited to participate.…”
Section: Participantsmentioning
confidence: 99%
“…A family cohort study from 2009–2011 reported a hypertension prevalence rate of 31.6% among adults aged 20 years and older in Hong Kong …”
Section: Current Status Of Hbpm In Asiamentioning
confidence: 99%
“…The control of hypertension in Malaysia was 33.3% (29.1-39.2) and this is much lower than that in developed countries such as United States (53%) [13]. On the other hand, this figure is higher than nearby countries like China (13.8%) [69, 84], Hong Kong (25.8%) [69, 98] and Philippines (27.0%) [69, 99]. This could be due to the fact that Malaysia has been improving health care facilities with more clinics and hospitals being built ensuring better access to health care [100].…”
Section: Discussionmentioning
confidence: 99%